Porous Carbon Architecture Assembled by Cross-Linked Carbon Leaves with Implanted Atomic Cobalt for High-Performance Li–S Batteries - Wang, Ruirui; Wu, Renbing; Ding, Chaofan; Chen, Ziliang; Xu, Hongbin; Liu, Yongfeng; Zhang, Jichao; Ha, Yuan; Fei, Ben; Pan, Hongge (Nano-Micro Letters, 2021)
The practical application of lithium–sulfur batteries is severely hampered by the poor conductivity, polysulfide shuttle effect and sluggish reaction kinetics of sulfur cathodes. Herein, a hierarchically porous three-dimension (3D) carbon architecture assembled by cross-linked carbon leaves with implanted atomic Co–N4 has been delicately developed as an advanced sulfur host through a SiO2-mediated zeolitic imidazolate framework-L (ZIF-L) strategy. The unique 3D architectures not only provide a highly conductive network for fast electron transfer and buffer the volume change upon lithiation–delithiation process but also endow rich interface with full exposure of Co–N4 active sites to boost the lithium polysulfides adsorption and conversion. Owing to the accelerated kinetics and suppressed shuttle effect, the as-prepared sulfur cathode exhibits a superior electrochemical performance with a high reversible specific capacity of 695 mAh g−1 at 5 C and a low capacity fading rate of 0.053% per cycle over 500 cycles at 1 C. This work may provide a promising solution for the design of an advanced sulfur-based cathode toward high-performance Li–S batteries. Highlights: 1 SiO2-mediated ZIF-L is developed to prepare Co–N4@2D/3D carbon. 2 Co–N4@2D/3D integrates the advantages of 0D Co single atom and 2D/3D carbon support. 3 Co–N4@2D/3D carbon-based sulfur cathode enables a high reversible specific capacity and low capacity fading rate.